SISTEM PENDETEKSI MUSUH DI POS DAERAH KONFLIK MENGGUNAKAN SENSOR GEOPHONE PADA MALAM HARI BERBASIS ARDUINO UNO: Elkasista - Irfan Fachrudin Priyanta; Sofyan Widodo; Fajar Kholid (Pustaka Poltekad, 2022)
Abstract: The post of the conflict area in Papua at night is in danger of an enemy approaching silently. Thus, resulting in material and personnel losses. To minimize personnel and material losses, it is necessary to have a silent enemy detector with efficiency and high effectiveness. The purpose of this study is to help post guards in conflict areas so that the level of vigilance at night is higher. For this reason, researchers made a tool that is able to detect enemies at night using geophone sensors by planting them in the ground and sent to the post using the NRF24L01 radio frequency after being processed by Arduino uno. In this study, experimental methods are used to achieve maximum results and will focus on geophone sensors, experiments carried out when the sensors are planted in the ground to detect vibrations that occur when there are humans around the post. The geophone sensor will detect the frequency that occurs when around the postal area there are humans walking. From the frequency data that has been concluded, you will get data that vibrations that occur when humans are around the post that has been processed by Arduino Uno are then sent via radio frequency and a warning will appear on the post in the form of LED lights and buzzer sounds that are like the sound of crickets. With this detection device, the security of posts in conflict areas is more maintained and safer at night. Keywords: Geophone Sensor, NRF24L01, Arduino Uno.